Phenotypic expression of schizotypy as a function of gender and age in the general adolescent population - Fonseca Pedrero, Eduardo; Paino, Mercedes; Lemos Giráldez, Serafín; Sierra Baigrie, Susana; Santarén Rosell, Marta; Ordoñez Camblor, Nuria; Muñiz, José (Anales de Psicología / Annals of Psychology, 2011)
The main objective of the present study was to examine the influence of gender and age in the phenotypic expression of schizotypy in two representative samples of Spanish adolescents. The first sample was composed of a total of 1,618 participants (M = 15.9 years; SD = 1.2) and the second sample was composed of 1,455 adolescents (M =15.9 years, SD = 1.2). The ESQUIZO-Q: Cuestionario Oviedo para la Evaluación de la Esquizotipia-Abreviado (The Oviedo Schizotypy Assessment Questionnaire-Brief) (Fonseca-Pedrero et al., 2010) was used for the assessment of schizotypal traits. Gender and age were found to be two sociodemographical variables that influenced the expression of schizotypal traits in adolescents. In regard to gender, the males in the first sample obtained higher mean scores than the females in the Negative dimension; however, the females obtained higher mean scores in Social Disorganization. In the second sample, the males obtained higher mean scores than the females in the Negative and the Reality Distortion dimensions. In regard to age, in the first sample, the younger adolescents scored higher in Social Disorganization compared to the older adolescents. In the second sample, the younger adolescents obtained higher scores than the older adolescents in the Negative dimension. In all cases the effect sizes were small (except Negative). In convergence with the previous literature, this differential pattern is similar to that found in patients with schizophrenia and in nonclinical adults, and contributes to our comprehension of the phenotypic expression of schizotypy during this developmental period.